Análise das Componentes do Balanço Energético numa Lavoura de Arroz Irrigado - Sena, Julio; Carneiro, Janaina; Michelon, Daniel; Teichrieb, Cláudio; Sehenem, Josué; Roberti, Débora; Zimermann, Hans; Webler, Geovane (Ciência e Natura, 2011)
.